Influence of yttrium element on the corrosion behaviors of Mg–Y binary magnesium alloy - Xianbin Liu (Journal of Magnesium and Alloys, 2017)
The influence of yttrium on the corrosion behavior of Mg–Y alloys has been investigated by electrochemical measurements, scanning electron microscope (SEM) observation, X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS) analysis in NaCl solution. The corrosion resistance decreased with increasing Y content due to increasing Y-rich zone. The solid-dissolved Y improved the chemical activity of the substrate which promoted the corrosion reaction by forming Y2O3. The corrosion resistance was improved by increasing the Y concentration of matrix and proper net Y-rich structure. The sample has the best corrosion resistance when all the Y element was dissolved into the matrix of Mg–5Y in 0.1 M NaCl. Keywords: Mg–Y alloys, Corrosion behavior, Yttrium element, Solid-dissolved Y